Spinocerebellar Ataxia - Concepts, Particularities and Generalities 2022
DOI: 10.5772/intechopen.104605
|View full text |Cite
|
Sign up to set email alerts
|

Living and Coping with Spinocerebellar Ataxia: Palliative Care Approach

Abstract: The discussion about the palliative care approach in spinocerebellar ataxia (SCA) has become extremely relevant. Mainly after considering that most progressive ataxias are incurable, there are few published studies on their palliative and end-of-life care. Although many patients with degenerative neurological diseases have a normal life expectancy, some forms of SCA (e.g., type 1, 2, 3, and 17) can progress rapidly, with a shorter life span. This chapter will discuss current guidelines and recommendations that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The cerebellar ROIs included the deep cerebellar nuclei (DCN)—the fastigial, interposed, and dentate nuclei (Purves, Augustine, & Fitzpatrick, 2001; Rajasekhar, 2022)—and the cerebellar lobules VI, crus I and II. The ROIs were extracted from the Montreal Neurological Institute (MNI) probabilistic atlas for cerebellar lobules and deep nuclei (Diedrichsen, Balsters, Flavell, Cussans, & Ramnani, 2009; Diedrichsen et al, 2011) (see also https://www.diedrichsenlab.org/imaging/propatlas.htm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebellar ROIs included the deep cerebellar nuclei (DCN)—the fastigial, interposed, and dentate nuclei (Purves, Augustine, & Fitzpatrick, 2001; Rajasekhar, 2022)—and the cerebellar lobules VI, crus I and II. The ROIs were extracted from the Montreal Neurological Institute (MNI) probabilistic atlas for cerebellar lobules and deep nuclei (Diedrichsen, Balsters, Flavell, Cussans, & Ramnani, 2009; Diedrichsen et al, 2011) (see also https://www.diedrichsenlab.org/imaging/propatlas.htm).…”
Section: Methodsmentioning
confidence: 99%
“…Purkinje cells are the sole output cells of the cerebellar cortex and they project to the three Deep Cerebellar Nuclei (DCN): the fastigial, interposed, and dentate nuclei (Purves, Augustine, & Fitzpatrick, 2001; Rajasekhar, 2022). A small number of studies have reported that the DCN project to the ventral tegmental area (VTA), a midbrain nucleus that plays a key role in motivated behavior as the origin of many dopaminergic cell bodies (Novello et al, 2022).…”
Section: Introductionmentioning
confidence: 99%